Female perspective: the burden of Alzheimer's disease and other dementias in China from 1990 to 2019 and prediction of their prevalence up to 2044 - Meng, Wenxin; Xie, Jinping; Yuan, Ni; Liu, Pingyu; Yang, Fan; Jiang, Rong; Hua, Hui (Frontiers in Public Health, 2023)
Abstract Background: Dementia affects more females than males, and sex differences exist in the burden of dementia. However, few studies have specifically analyzed the disease burden of dementia in Chinese women. Objective: This article aims to raise awareness to CFWD, outline an effective response to future trends in China from a female perspective, and provide reference for scientific formulation of prevention and treatment policies in China. Methods: In this article, epidemiological data on dementia in Chinese women were obtained from the Global Burden of Disease Study 2019, and three risk factors, smoking, high body mass index, and high fasting plasma glucose, were selected for analysis. This paper also predicted the burden of dementia in Chinese women in the next 25 years. Results: Prevalence, mortality, and disability-adjusted life years rates increased with age in Chinese females with dementia in 2019. All three risk factors provided by the Global Burden of Disease Study 2019 showed positive correlations for the effect of disability-adjusted life years rates in Chinese females with dementia. Among them, high body mass index had the greatest effect (8%) and smoking had the smallest effect (6.4%). Over the next 25 years, the number of Chinese females with dementia and prevalence are on the rise, while mortality is relatively stable and declining slightly, but deaths from dementia will continue to increase. Conclusions: The situation of dementia in Chinese women in the future is serious. To reduce the burden of dementia, the Chinese government should prioritize prevention and treatment. A multi-dimensional, long-term care system involving families, community, and hospitals should also be established and supported.